Penanaman Pendidikan Multikultural pada Masyarakat Melalui Pendirian Rumah Ibadah Bersama - Mujiyanto Mujiyanto (Faculty of Psychology, Universitas Semarang, 2018)
This study aims to find out how to cultivate multicultural education to the community, what lies behind the establishment of a shared house of worship in a neighborhood location of the Boyolali Regency Government, and how the conditions of harmony among religious communities in Boyolali Regency. The results of this study indicate that: (1) Multicultural education has been going well and has been socialized by religious leaders and leaders through various formal and non-formal activities in places of worship and in schools; (2) Establishment of places of worship on the initiative of the Boyolali Regent and supported by religious and masayarak leaders, with the aim of building togetherness to overcome differences, and to create harmony of religious life; (3) Religious harmony in Boyolali Regency has been going well, there has never been a conflict between followers of different religions.